Lactation suppression. - Calderón Morales, Jorge (2015)
In order to evaluate a new dopaminergic prolactin inhibitor: lisuride hydrogen maleate (Dopergin R), in suppression of lactation; It was administered to 48 patients a dose of 0.2 mg. the first day postpartum, 0.4 mg. the second day and 0.6 mg. from the 3rd. to 14th. day, the results were very satisfactory. In 45 patients (93.75%) the total suppression of lactation and 47 patients (97.91%) had no side effects at the end of the prospective study was achieved. Only one patient (2%) had mild nausea until the end of the study. The most common clinical indication was to neonatimuertos 21 cases (43.75%) and the most common cause of perinatal mortality was severe preeclampsia in 10 cases (20.82%). Other indications were fetal deaths, stillbirths and late abortions. In conclusion we believe Hidrogen lisuride maleate is an effective and tolerable product in patients in whom its use in inhibition of lactation, compared to bromocriptine and other methods with lower degree of effectiveness is less tolerable by patients is necessary.